ANALISIS KETERAMPILAN MEMBACA PERMULAAN PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS 1 SD - Destiyani Safitri; Rina Yuliana; Yoma Hatima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the planning process, teacher strategies, and instructional activities related to early reading skills in Indonesian language learning for first-grade students at SDN Kalideres 14 Petang. This research employed a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that in the planning phase, teachers develop teaching modules tailored to learning outcomes, student needs, and the current curriculum. Instructional strategies involve four key components, teaching materials, methods, media, and learning resources, selected based on diagnostic assessments and student characteristics. Learning activities are carried out in a gradual and interactive manner using contextual approaches that incorporate images, songs, games, and the surrounding environment to enhance student motivation and comprehension. The learning process covers five indicators of early reading skills: recognizing letters, reading meaningful and non-meaningful words, reading aloud with comprehension, and listening to texts. This research is expected to serve as a reference for educators and future researchers in improving early reading instruction at the elementary level.